Licensing Adaptive Immunity by NOD-Like Receptors - Liu, Dong; Rhebergen, Anne Marie; Eisenbarth, Stephanie C. (Frontiers in Immunology, 2013)
The innate immune system is composed of a diverse set of host defense molecules, physical barriers and specialized leukocytes and is the primary form of immune defense against environmental insults. Another crucial role of innate immunity is to shape the long-lived adaptive immune response mediated by T and B lymphocytes. The activation of pattern recognition receptors (PRRs) from the Toll-like receptor family is a now classic example of innate immune molecules influencing adaptive immunity, resulting in effective antigen presentation to naïve T cells. More recent work suggests that the activation of another family of PRRs, the NOD-like receptors (NLRs), induces a different set of innate immune responses and accordingly, drives different aspects of adaptive immunity. Yet how this unusually diverse family of molecules (some without canonical PRR function) regulates immunity remains incompletely understood. In this review, we discuss the evidence for and against NLR activity orchestrating adaptive immune responses during infectious as well as non-infectious challenges.